An evaluation of the feasibility of implementing the BeWEL lifestyle intervention programme for people at increased risk of colorectal cancer – from research to real life. Issue 2 (8th December 2022) - Anderson, Annie S.; Donaghy, Claire; Lamb, Ross; Steele, Robert J. C.; Moug, Susan
Abstract: Background: The BeWEL randomised controlled trial (RCT) of weight loss in people with colorectal adenomas demonstrated that a significant proportion of people are interested in lifestyle interventions (49%) and clinically relevant changes in body weight were achieved at 12‐month follow‐up. The current work aimed to assess the feasibility of the BeWEL programme invitation and delivery in a nonresearch setting to assess whether the original results could be replicated. Methods: The original BeWel programme was modified through the provision of verbal introductions (vs. letter), requirement for people to contact BeWEL team (vs. BeWEL team contacting them), community delivery (vs. home), duration (12 weeks vs. 12 months) and two intervention visits (vs. 3) and inclusion of people with predisposition to colorectal cancer. Eligible people were informed about the BeWel programme from National Health Service (NHS) staff after colonoscopy procedures and invited to contact a dedicated Bowel Cancer UK lifestyle team. Results: Findings demonstrated that programme uptake (10.6% vs. 33%) and retention (71% vs. 93%) was significantly lower than that obtained from the BeWEL RCT. For people who participated in the 3‐month programme ( n = 21), self‐reported weight loss (mean: −7% body weight) was successful, and the programme was well received. Conclusions: The current approach to engaging clients with the BeWEL programme is unsustainable. Reliance on busy NHS staff to deliver invitations and the need for people to contact the delivery team (due to data protection) may have impacted on uptake. Alternative approaches to supporting weight management in this population should be explored further. Key points: Despite successful engagement and outcomes in the BeWEL trial, roll‐out in clinical practice was characterised by staff challenges and data protection issues, although weight loss in participants was clinically relevant.